2015
DOI: 10.1021/acs.joc.5b02008
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Light-Controlled Cargo Release in Hydrogen-Bonded Dimeric Capsules

Abstract: We describe the synthesis of three tetraureacalix[4]arenes having four appended terminal azobenzene groups. In CD2Cl2 solution and at millimolar concentration, the thermally equilibrated all-trans-tetraureas dimerize quantitatively, encapsulating one Me4P(+) cation. The light-induced isomerization of the all-trans encapsulation complexes produced a plethora of isomeric cis-enriched counterparts displaying a reduction in cavity size. cis-enriched dimers not suitable for the encapsulation of the cation or a solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 25 publications
2
39
0
Order By: Relevance
“…This has led to viable approaches towards intelligent supramolecular materials, molecular information processing, the release/capture of compounds in bio‐inspired applications, and drug‐delivery systems . Among other stimuli, such as chemical and electrochemical signals, the use of light has been a preferred choice due to the possibility of conducting spatiotemporally and remotely controlled experiments . Our own efforts in this field have focused on supramolecular complexes with cucurbituril hosts and their manipulation by means of photoinduced pH jumps .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to viable approaches towards intelligent supramolecular materials, molecular information processing, the release/capture of compounds in bio‐inspired applications, and drug‐delivery systems . Among other stimuli, such as chemical and electrochemical signals, the use of light has been a preferred choice due to the possibility of conducting spatiotemporally and remotely controlled experiments . Our own efforts in this field have focused on supramolecular complexes with cucurbituril hosts and their manipulation by means of photoinduced pH jumps .…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8][9][10][11] Among other stimuli,s uch as chemical and electrochemicals ignals, the use of light has been ap referred choice due to the possibility of conducting spatiotemporally and remotely controlled experiments. [1,[12][13][14][15][16] Our own efforts in this field have focused on supramolecular complexes with cucurbituril hosts and their manipulation by means of photoinduced pH jumps. [17,18] The choice of cucurbiturils as hostm acrocycles for these applications is motivated by their unique supramolecular chemistry,i ncludinge xtraordinary high binding constants for avariety of organic guests in water.…”
mentioning
confidence: 99%
“…Likewise, also the host can be equipped with a photoisomerizable group, enabling the opening or closing of a capsule. Such systems were reported, for example, by the Ballester group, drawing on calix[4]arenes with appended azobenzenes as light‐sensitive units of self‐assembled capsules . These light‐responsive assemblies could be potentially implemented for chemical communication.…”
Section: Release Of Guests From Supramolecular Assembliesmentioning
confidence: 99%
“…These photoswitchable molecules self‐assembled in dimeric capsules and showed that their trans ‐to‐ cis photo‐isomerization induced the release of the encapsulated organic cation (e.g. tetramethylphosphonium) to the bulk solution . Rebek and co‐workers attached one azobenzene group to a deep cavitand derived from a resorcin[4]arene scaffold , .…”
Section: Introductionmentioning
confidence: 99%